2013
DOI: 10.1007/s11010-013-1855-8
|View full text |Cite
|
Sign up to set email alerts
|

IGF-1 gene-modified muscle-derived stem cells are resistant to oxidative stress via enhanced activation of IGF-1R/PI3K/AKT signaling and secretion of VEGF

Abstract: Reactive oxygen species (ROS)-induced oxidative stress increases in skeletal muscle with aging and decreases the viability of implanted cells. Type 1 insulin-like growth factor (IGF-1) promotes the survival of skeletal muscle cells under oxidative stress. It is unknown whether IGF-1 protects muscle-derived stem cells (MDSCs) from oxidative stress. In this study, we genetically engineered rat MDSCs to overexpress IGF-1 and determined cell viability, apoptosis, and VEGF secretion under oxidative stress. Overexpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 36 publications
2
23
0
Order By: Relevance
“…From recent studies it can be suggested that MSCs have two populations: nestin positive and nestin negative [1]. Some research suggests that the MSCs express the nestin when they are under stress [21, 22]. However, further research is warranted to characterise the two populations of the MSCs and trace their origins.…”
Section: Discussionmentioning
confidence: 99%
“…From recent studies it can be suggested that MSCs have two populations: nestin positive and nestin negative [1]. Some research suggests that the MSCs express the nestin when they are under stress [21, 22]. However, further research is warranted to characterise the two populations of the MSCs and trace their origins.…”
Section: Discussionmentioning
confidence: 99%
“…16 In addition, treatment with OSI-906, an inhibitor of IGF-1R, is synergistic with BTZ and resensitizes BTZ-resistant cells to BTZ treatment. 16 Of note, IGF-1R signaling has been linked to attenuation of oxidative stress in muscle cells 48 ; however, subsequent studies will be needed to determine whether inhibiting IGF-1R in MM cells affects TIGAR and ROS. In the present work, BTZ-resistant MM cells were shown to be as sensitive to targeting MUC1-C as their drug-naïve counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…These include cellular protective pathways of phosphoinositide 3 –kinase (PI 3-K) and protein kinase B (Akt) [5663] as well as forkhead transcription factors, sirtuins, and the mechanistic target of rapamaycin (mTOR). For example, activation of Akt limits cell injury and prevents the detrimental effects of amyloid (Aβ) toxicity [21, 64, 65] and oxidative stress [6669].…”
Section: Wisp1 Signalingmentioning
confidence: 99%
“…EPO utilizes Akt to block cell injury during Aβ exposure [26], promote the survival of retinal ganglion cells during N-methyl-d-aspartate (NMDA) toxicity [73], enhance the myocardial protective function of mobilized peripheral blood mononuclear cells [74], foster anti-inflammatory effects [75], protect against sepsis [76], limit renal cell injury [77], and limit cellular injury during models of oxidative stress [7881]. Similar to EPO, other trophic factors also rely upon the PI 3-K and Akt pathways to foster cellular survival during toxic environments such as insulin-like growth factor-1 (IGF-1) [56], insulin [82], and brain derived neurotrophic factor [83]. …”
Section: Wisp1 Signalingmentioning
confidence: 99%
See 1 more Smart Citation